Seni Tradisional Wayang Kulit sebagai Media Dakwah Islam di Jawa - Sanihah, Mutia - (Maliki Interdisciplinary Journal, 2025)
Wayang kulit as part of Indonesian cultural heritage plays an important role in conveying Islamic da’wah in Java. This article aims to examine the history of wayang kulit as a medium of da’wah and the important contribution of Sunan Kalijaga in its development in the region. Through an in-depth literature review, this study explores the concept of da’wah in Javanese Islam, the development of wayang kulit as a medium for conveying religious messages, and how Sunan Kalijaga succeeded in integrating Islamic values ​​with Javanese culture through performing arts. A literature study approach is applied to analyze and interpret various findings from related literature, which show that wayang kulit is not only a traditional entertainment medium, but also an effective means of education and da’wah. The results of the study indicate that wayang kulit plays an important role in strengthening Islamic identity in Javanese society and conveying moral and spiritual messages that are relevant to local culture. These findings also highlight the relevance of wayang kulit in the modern era, providing deep insight into how this traditional performing art is able to survive and adapt in the face of changing times. This article recommends a new approach in viewing the potential of da’wah through traditional arts such as wayang kulit, and emphasizes the need for strategies to maintain the sustainability and preservation of this cultural heritage in the future.